Research advances on the role of Runx2-related miRNAs in vascular calcification of chronic kidney disease - Lu Yang-yang; Bai Ya-ling; Xu Jin-sheng (Linchuang shenzangbing zazhi)
Vascular calcification （VC） is a major cause of cardiovascular mortality in patients with chronic kidney disease （CKD）. Current studies suggest that VC of CKD is not simply an ectopic deposition of calcium phosphate crystals in vascular wall. Formation of calcification has a similar mechanism to bone mineralization and smooth muscle cells play a key role in VC. Sufficient evidence suggested that Runx2 is an essential regulator of osteogenic differentiation and calcification in vascular smooth muscle cells. In recent years， multiple microRNAs have been identified as key regulators for differentiation of vascular smooth muscle cell， phenotypic switching， proliferation， apoptosis， cytokine production and matrix deposition during VC. This review focused upon the role of relevant microRNAs regulating Runx2 expression in osteogenic differentiation of smooth muscle cells. Since the exact mechanism of VC has remained largely elusive， a better understanding of microRNA involvement in VC may help to design novel therapies for VC.